Architects finding inspiration in Europe: Erasmus mundus program experiences - Mohd Yaacob, Naziaty; Tan, Pacilia Saw Kun (AEI Insights, 2021)
The European Union has run its higher-education exchange program “Erasmus Mundus” to enable the mobility of students and academics between Europe and other continents, including Asia since 2004. The benefits of studying abroad are multifold, but for most people it gives the once-in-a-lifetime chance to experience what they have read in books or heard about in lectures. In this paper we share our own study-abroad and staff mobility experiences which were enabled by the European Union’s Erasmus Mundus scholarship programs for 1. A senior lecturer of architecture at Universiti Malaya (UM) to conduct research as a visiting scholar at the University of Porto. 2. A recent graduate in architecture degree from UM to study for a master’s degree in the same discipline at the Milan Polytechnic. For the young student, living and studying outside of Malaysia for the first time was exciting and challenging, whereas for the experienced academic, who used to live and study in the U.S.A. and U.K., her month-long experience in Porto was rejuvenating her passion for architecture, travel and life despite her disability. After finishing their programs, they both returned to Malaysia. In this paper, they share the impacts of their Erasmus Mundus programs on their personal and professional lives.